Joint Controller Method: Application in 3D Humanoid Style Deformation - Ismail, Ismahafezi; A. Abuhashish, Faris; Nor Wan Shamsuddin, Syadiah Nor; Mat Amin, Maizan; Kufaisal Mohd Sidik, Mohd (International Journal of Engineering and Technology, 2018)
Realistic 3D humanoid style deformation is an attractive topic especially for the industries developing computer animations and games. Calculating the correct position style is a challenging task due to 3D humanoid complex dimensional data. Axis of interest and angle of rotation are two parameters measured in this real-time application. The main contribution of this article is through the development of joint controller method for controlling body position, orientation and joint rotation to produce style deformation. This method allows the deformation of new 3D humanoid styles by users using a simple interface control. This style joint controller method can help researchers to setup their motion editor and synthesis system.